Development of Religious Culture in The School Community - Khadavi, Jadid (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
The school's religious culture is an effort to realize the values ​​of religious teachings as a tradition in behavior and organizational culture that is followed by all members of the school. By making religion a tradition in schools, consciously or not, when the school members follow the traditions that have been ingrained, the school members are already practicing religion. Cultivating religious (religious) values ​​can be done in several ways, including through: school leadership policies, implementation of teaching and learning activities in class, extracurricular activities, as well as consistent traditions and behavior of school members, so as to create a religious culture within educational institutions. This study provides an overview of the development of religious culture that has been carried out in school institutions/agencies in general. Bias often occurs in understanding religious culture and religious atmosphere. These two things have significant differences. So, this study is expected to be able to provide an overview of the practice of developing religious culture